Evaluasi Program Jaminan Kesehatan Nasional Pada Fasilitas Kesehatan Tingkat I Kabupaten Sleman Tahun 2016 - Utami, Andi Nur Fiqhi; Mutiarin, Dyah (Journal of Governance and Public Policy, 2017)
National Health Insurance Program is held BPJS Health is an insurance program that helps communities in order toimprove community health status. BPJS Health is a legal entity formed to administer the health insurance program. Thus,this research is very important as the evaluation of health care programs implemented JKN BPJS in Sleman. This studyused mix-method research methods or a combination of qualitative research and quantitative. Thus, the method of datacollection using surveys and interviews, accompanied by direct observation in the field. The research location is in thedistrict of Sleman, precisely at the level of health facilities I. While the process of data analysis in this study begins with thisdata collection, mengkodefikasi the data, calculate the index, interpret the data, categorize data and linking the findings.Based on the results of the study, the authors found that people's judgment JKN Program is organized by the Health BPJSin Sleman district on a service model gets pretty good value, and the quality of service also get pretty good value.Although there are some problems such as the lack of public knowledge at the service model, and problems in the workforce, but queried the whole program is going pretty well